A Diabetes and Obesity Crisis: Preliminary Study of Lifestyle, Diet, Knowledge and Attitude of Malaysian Pharmacy Undergraduates Towards Type-2 Diabetes - Shariza Sahudin,; Mumtaz Hussain,; Nor Farhah Abdul Ghaffar ,; Azyyati Mohd Suhaimi, (Journal of Pharmacy and Nutrition Sciences, 2017)
Background: Patient education and self-care are important not only for diabetes prevention but also chronic disease management. Community pharmacists are an ideal position to play a role in providing medicines management, lifestyle and preventative advice specific to type-2 diabetes care, Malaysian pharmacists must be ready and willing to firmly establish such clear roles and as such, undergraduate pharmacy students need to be equipped with the skills and mind-set to accept such a challenge Objective: To explore knowledge and awareness of pharmacy undergraduate students at Universiti Technology MARA (UiTM) towards diabetes risk factors. To identify potential diabetes risk factors by evaluating dietary intake and to determine students’ attitude towards their future roles as health care providers. Method: 159 Malaysian third-year undergraduate pharmacy students were provided a questionnaire and a two-day food diary. The questionnaire consisted of four sections to examine demographics, lifestyle and diet, together with knowledge of diabetes and the perception of pharmacists’ role. Results: A total of 113 completed questionnaires were received. 20% of the respondents were overweight or obese and 21% had elevated blood pressure. 95% of students consumed only 50% of the recommend daily calorie intake for adults. Students however possessed good knowledge of diabetes with a positive attitude towards pharmacist roles in healthcare. Conclusion: Overall, the health status of Malaysian pharmacy students is very similar to the general population, displaying similar risk factors and dietary habits despite their status as future healthcare professionals. Students do however display a good knowledge of diabetes and appear positive towards their roles as future pharmacists.